Validation Assessment of a Relationship between Teaching Practice and Professional Engineer Certification: A Pilot Study and Survey Evaluation (Asean Journal of Engineering Education, 2023)
Engineering courses are regarded as challenging that require a solid foundation in mathematics, physics, and chemistry as well as critical thinking and problem-solving skills. Inadvertently, these components present challenges to the teaching and learning (T&L) process in the classroom and up to the author's knowledge, there is no study reported in relation with professional engineer certification and UTM-NALI teaching practices. Therefore, this study examined the relationship between engineering educators with professional engineer certification and their teaching methods in particular UTM-NALI. This is a pilot study with small respondents and to validate survey questions for assessment in larger samples. Additional questions regarding the obstacles, recommendations, and example characteristics are also offered. The data on the performance of students and the distinction between certified and uncertified lecturers are discussed. Through their participation in T&L in the classroom, lecturers with and without professional engineer qualifications can be seen experiencing the effects of the NALI model. Even though hybrid classes that were conducted to help pupils catch up with previous Malaysian MCOs (movement control orders) can limit this study, through the test findings, this study can be carried out for larger samples to get congruent conclusions of proposed research.
Keywords: NALI; Professional Engineer Certification; Teaching Practice; Teaching and Learning; Validation Assessment